Relação entre os níveis de citocinas e parâmetros de resposta terapêutica da hiperglicemia em idosos com diabetes mellitus - Lacerda, Wendell Sanchez (2018)
In individuals with Diabetes Mellitus type 2 (DM2), as a result of oxidative stress caused by the maintenance of Hyperglycemia is increased production of cytokines that modulate various phenomena of cellular activity reverberating in the response individual's immune and cardiovascular complications. Thus, the objective of this study was to relate the glycemic values with the pro-and anti-inflammatory cytokines levels present in the serum of elderly patients with DM. Serum samples were collected from 32 individuals with body mass index (BMD) > 25 Kg/m? and 39 Kg/m ?, between 60 to 90 years and with previous diagnosis of DM? (16) and without DM? (16) (ND). Were evaluated in the serum concentrations of cytokines (IL-1 B, IL6, IL-8, IL-10, IL-12 and TNF), by the method of flow cytometry as well as levels of superoxide Dismutase (SOD). Have also been measured in patients of the control group and the study biochemical markers like cardio-cérebrovasculares risk factors, among them: PCR-us, lipid profile, as well as monitoring elements of hyperglycemia such as glycated haemoglobin. On comparison between diabetics and non-diabetics, the first under exclusive use of hypoglycemic drugs and compliance with the glucose goals, and with just overweight, an increase in the expression of IL-10, associated with the inhibition on the expression of IL-6, IL-1 6 and T'NF, revealing a metabolic-immune performance satisfactory, in spite of the senescence that affects the study groups. These data suggest that the glycemic control promotes the expression of IL10 which has key role in inhibiting the expression of pro-inflammatory cytokines such as IL-6 and TNF, this mechanism may be an important therapeutic strategy in patients with persistent hyperglycemia.